The USH3A causative gene clarin1 functions in Müller glia to maintain retinal photoreceptors. - Hannah J T Nonarath; Samantha L Simpson; Tricia L Slobodianuk; Hai Tran; Ross F Collery; Astra Dinculescu; Brian A Link (PLoS Genetics)
Mutations in CLRN1 cause Usher syndrome type IIIA (USH3A), an autosomal recessive disorder characterized by hearing and vision loss, and often accompanied by vestibular dysfunction. The identity of the cell types responsible for the pathology and mechanisms leading to vision loss in USH3A remains elusive. To address this, we employed CRISPR/Cas9 technology to delete a large region in the coding and untranslated (UTR) region of zebrafish clrn1. The retinas of clrn1 mutant larvae exhibited sensitivity to cell stress, along with age-dependent loss of function and degeneration in the photoreceptor layer. Investigation revealed disorganization in the outer retina in clrn1 mutants, including actin-based structures of the Müller glia and photoreceptor cells. To assess cell-specific contributions to USH3A pathology, we specifically re-expressed clrn1 in either Müller glia or photoreceptor cells. Müller glia re-expression of clrn1 prevented the elevated cell death observed in larval clrn1 mutant zebrafish exposed to high-intensity light. Notably, the degree of phenotypic rescue correlated with the level of Clrn1 re-expression. Surprisingly, high levels of Clrn1 expression enhanced cell death in both wild-type and clrn1 mutant animals. However, rod- or cone-specific Clrn1 re-expression did not reduce the extent of cell death. Taken together, our findings underscore three crucial insights. First, clrn1 mutant zebrafish exhibit key pathological features of USH3A; second, Clrn1 within Müller glia plays a pivotal role in photoreceptor maintenance, with its expression requiring controlled regulation; third, the reliance of photoreceptors on Müller glia suggests a structural support mechanism, possibly through direct interactions between Müller glia and photoreceptors mediated in part by Clrn1 protein.